Cystic biliary atresia with paucity of bile ducts and gene mutation in KDM6A: a case report - Daisuke Masui; Suguru Fukahori; Tatsuki Mizuochi; Yoriko Watanabe; Kaori Fukui; Shinji Ishii; Nobuyuki Saikusa; Naoki Hashizume; Naruki Higashidate; Saki Sakamoto; Aiko Takato; Koh-ichiro Yoshiura; et al. (Surgical Case Reports)
Abstract Background Biliary atresia (BA) cases are generally not associated with congenital abnormalities. However, accurate diagnosis of BA is often challenging because the histopathological features of BA overlap with those of other pediatric liver diseases and rarely overlap with those of other genetic disorders. We experienced a rare case of BA with the histopathological finding of bile duct paucity, a gene mutation in KDM6A, and KS-like phenotypes. Case presentation A male baby was diagnosed with biliary atresia by intraoperative cholangiography at 4 days of age, and histological examination following a liver biopsy revealed a paucity of bile ducts and several typical clinical findings of Alagille syndrome. However, Alagille syndrome was ruled out after neither JAG1 nor NOTCH2 gene mutations were identified. Whole-exome sequencing on DNA from his parents was additionally performed to examine other possible syndromic disorders, and a mutation was identified in KDM6A. However, Kabuki syndrome was not diagnosed as a result. The histological finding of interlobular bile duct paucity and the genetic mutation in KDM6A, as well as several clinical findings consistent with Alagille syndrome or Kabuki syndrome, made it difficult to confirm the diagnosis of BA. Conclusions Based on the interesting findings of the present case, we hypothesized that KDM6A is associated with hepatic malformations via a connection with the Notch signaling pathway.